« A Woman’s Answer » : Adelaide Procter et la poésie face au genre - Fabienne Moine (Cahiers Victoriens et Edouardiens)
To avoid being trapped in the fury of feminist claims and to spurn the traditional gender ideology, some Victorian women poets take up a third discourse, ambiguous and protean. Adelaide Procter (1825–1864) chooses neither to fight nor to accept gender ideology. Her faith-driven poetry enables her to write in-between poems, keeping away from official authoritarian discourses, which support or deny the existence of gender spheres. Thus, Procter, as a feminist, writes poems defending feminine values whilst resisting to self-deprecation and to the excessive enhancement of virtues. Converted to Catholicism in 1851, Procter, as a Tractarian, uses her poetry, both religious and feminist, as a weapon against the construction of political and poetical patterns. Being Anglo-Catholic, she can create a feminine and autonomous space from where she gives her own interpretations and turns away from official discourses.